Internationalization Strategies and Performance of Multinational Companies in Nigeria - Adeleke, Sakiru Ademola; Owolabi, Sunday; Akintoye, Ishola Rufus (Archives of Business Research, 2022)
The challenges of firm performance of international companies and assessment of corporate strategies have witnessed fundamental changes in literature far beyond book values. A consideration of comprehensive integration and inadequate overlap among firm performance drivers, and declining comparative competitive advantage in the industry where the multinational companies operate are significantly unsettling. The study adopted an ex-post facto research design. The survey was conducted across three (3) sectors of the Nigeria Stock exchange with the population of one hundred and seventy-one (115) companies. The study used a purposive sampling technique to select the international companies. Hence, a sample size of sixteen (16) multinational companies is used to investigate the effect of internationalization and firm performance. Secondary data was adopted for the study and the data for the study were obtained from the Nigerian Stock Exchange Annual report; annual reports and financial statements of the selected companies. Descriptive and inferential (Panel regression analysis) were used to analyse the data. Hausman test was conducted to determine the choice of model to use between the fixed effect model or random effect model. The study revealed two models. One model without control variables and the other with control variable. Model one shows that internationalization has a significant effect on firm performance of listed companies in Nigeria revealing an adjusted r square of 0.0913; Wald Stat of 18.30 and the p-value of 0.000 < 0.05. Model two also revealed a significant effect with an adjusted r square of 0.252, F statistic of 9.93 and p-value of 0.000 < 0.05. The study, however, concluded that internationalization has a significant effect on firm performance of listed companies in Nigeria. Therefore, it was recommended that management of multinational companies should review and re-engineer the dynamics of export intensity to improve the performance of companies to efficiently and effectively generate profits using its assets. . The government and policymakers should reconsider charges and interest rates to accommodate the loan facilities of the multinational companies. Management should put in place investment policies that will attract foreign investors in the company which will enhance operations and performance. Management should take advantage of their strength and emerging opportunities to enhance company sales.